1995
DOI: 10.1002/arch.940300211
|View full text |Cite
|
Sign up to set email alerts
|

Pathway and regulation of JHIII‐bisepoxide biosynthesis in adult Drosophila melanogaster corpus allatum

Abstract: Adult female Drosophila melanogaster corpus allatum (CA) synthesize JHB3 from endogenous and exogenous precursors in vitro. We present evidence supporting the thesis that biosynthesis proceeds from precursor FA via initial epoxidation and terminal methylation on the basis of the following: (1) Methyl farnesoate is not epoxidized to JHIII or JHB3; (2) Authentic JHIII is not epoxidized to JHB3; and (3) FABE is markedly metabolized to JHB3. Cerebral allatostatic factors act at some stage subsequent to FA and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 30 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…However, unlike in D. punctata, JH III bisepoxide (JHB 3 ) is thought to be the major JH produced in D. melanogaster (70). JHB 3 is synthesized by an alternate pathway possibly involving 2 epoxidation reactions catalyzed by a P450, converting farnesoic acid to JHB 3 (71). It is possible that this P450 is CYP6G2.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike in D. punctata, JH III bisepoxide (JHB 3 ) is thought to be the major JH produced in D. melanogaster (70). JHB 3 is synthesized by an alternate pathway possibly involving 2 epoxidation reactions catalyzed by a P450, converting farnesoic acid to JHB 3 (71). It is possible that this P450 is CYP6G2.…”
Section: Discussionmentioning
confidence: 99%
“…Severance in vitro of that connection removed the statin effect of the brain on ring gland secretion . Moshitzky and Applebaum (1995) reported bisepoxy JH III production in vitro by isolated (Days 2 and 3) adult CA was about 3 Â higher than brain-CA complexes.…”
Section: Cerebral Control Over Methyl Farnesoid Biosynthesismentioning
confidence: 94%
“…Richard et al (1989a) reported a significant change from the larval to adult stage in the proportion of ring gland product that is bisepoxy JH III Versus methyl farnesoate. Moshitzky and Applebaum (1995) showed that adult (mixed sexes) brain extract could modulate (i.e., suppress) in vitro biosynthesis of bisepoxy JH III (but not JH III and methyl farnesoate) in response to exogenous farnesoic acid. Those authors also showed that in vitro biosynthesis of methyl farnesoate is a specific end product of a branch of methyl farnesoid biosynthesis and that this end product is not further anabolized prior to secretion.…”
Section: Developmental Differences In Biosynthesis Of Specific Methylmentioning
confidence: 99%
“…comm.). According to the known biosynthesis pathway for each of these compounds in Drosophila , all three derive from mevalonate, the enzymatic product of hydroxymethylglutaryl CoA reductase (Belles et al, 2005; Moshitsky and Applebaum, 1995). Hence, the RNAi that is genetically targeted against HMGCR in the corpora allatal cells would necessarily inhibit production of all three methyl farnesoids.…”
Section: Methodsmentioning
confidence: 99%